Effects of varying training load on heart rate variability and running performance among an Olympic rugby sevens team - Flatt, A. A.; Howells, D. (Journal of Science and Medicine in Sport, 2019)
Objectives: To evaluate weekly heart rate variability (HRV) responses to varying training load among an Olympic rugby sevens team and to assess whether HRV responses informed on training adaptation. Design: Retrospective. Methods: Natural logarithm of the root mean square of successive differences (LnRMSSD), psychometrics and training load from a rugby sevens team (n = 12 males) over a 3-week period were retrospectively analyzed. Week 1 served as baseline while weeks 2 and 3 consisted of peak training loads from the 2016 Olympic preparatory period. Maximum aerobic speed (MAS) was evaluated at the beginning of weeks 1 and 3. Results: LnRMSSD (p = 0.68), its coefficient of variation (LnRMSSDcv) (p = 0.07) and psychometrics (all p > 0.05) did not significantly change across time. Effect sizes (ES) showed a small increase in LnRMSSDcv after the first week of intensified training (ES = 0.38) followed by a moderate reduction in week 3 (ES = -0.91). Individuals with a smaller LnRMSSDcv during the first week of intensified training showed more favorable changes in MAS (r = -0.74, p = 0.01), though individual changes only ranged from -1.5 to 2.9%. Conclusions: In week 3, players accomplished greater external training loads with minimal impact on internal load while wellness was preserved. Concurrently, players demonstrated less fluctuations in LnRMSSD, interpreted as an improved ability to maintain cardiac-autonomic homeostasis despite increments in training load. Monitoring the magnitude of daily fluctuations in LnRMSSD in response to varying training loads may aid in the evaluation of training adaptations among elite rugby players. ABSTRACT FROM AUTHOR